Urban agriculture as a keystone contribution towards securing sustainable and healthy development for cities in the future. Issue 1 (2nd December 2019) - Skar, S. L. G.; Pineda-Martos, R.; Timpe, A.; Pölling, B.; Bohn, K.; Külvik, M.; Delgado, C.; Pedras, C. M.G.; Paço, T. A.; Ćujić, M.; Tzortzakis, N.; Chrysargyris, A.; et al.
Abstract: Research and practice during the last 20 years has shown that urban agriculture can contribute to minimising the effects of climate change by, at the same time, improving quality of life in urban areas. In order to do so most effectively, land use and spatial planning are crucial so as to obtain and maintain a supportive green infrastructure and to secure citizens' healthy living conditions. As people today trend more towards living in green and sustainable city centres that can offer fresh and locally produced food, cities become again places for growing food. The scope of urban agriculture thereby is to establish food production sites within the city's sphere; for example, through building-integrated agriculture including concepts such as aquaponics, indoor agriculture, vertical farming, rooftop production, edible walls, as well as through urban farms, edible landscapes, school gardens and community gardens. Embedded in changing urban food systems, the contribution of urban agriculture to creating sustainable and climate-friendly cities is pivotal as it has the capacity to integrate other resource streams such as water, waste and energy. This article describes some of the current aspects of the circular city debate where urban agriculture is pushing forward the development of material and resource cycling in cities.